2016
DOI: 10.1098/rspb.2016.0414
|View full text |Cite
|
Sign up to set email alerts
|

Rising atmospheric CO2is reducing the protein concentration of a floral pollen source essential for North American bees

Abstract: At present, there is substantive evidence that the nutritional content of agriculturally important food crops will decrease in response to rising levels of atmospheric carbon dioxide, C a . However, whether C a -induced declines in nutritional quality are also occurring for pollinator food sources is unknown. Flowering late in the season, goldenrod (Solidago spp.) pollen is a widely available autumnal food source commonly acknowledged by apiarists to be essential to native bee (e.g. Bombus spp.) and honeybee (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 55 publications
0
77
1
1
Order By: Relevance
“…Bees are facing global declines owing to myriad factors, including reduced availability of high-quality forage [10][11][12]. Furthermore, modern agricultural practices, such as irrigation and pesticide use, have been demonstrated to alter the nutritional composition of floral nectar and pollen, and subsequently influence bee preferences and visitation rates [54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Bees are facing global declines owing to myriad factors, including reduced availability of high-quality forage [10][11][12]. Furthermore, modern agricultural practices, such as irrigation and pesticide use, have been demonstrated to alter the nutritional composition of floral nectar and pollen, and subsequently influence bee preferences and visitation rates [54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, flowers and leaves of herbarium specimens can contain signatures of interactions, such as the accumulation of defensive compounds induced by insect herbivores (Zangerl and Berenbaum ) and pollen (Ziska et al. ).…”
Section: Contributions Of Herbaria To Global Change Researchmentioning
confidence: 99%
“…In one of the few herbarium studies to explore how pollution affects species interactions, Ziska et al. () analyzed pollen preserved in herbarium specimens and demonstrated that elevated CO 2 concentrations reduced pollen protein concentrations, altering nutrient availability for pollinators, with possible fitness consequences for both pollinators and plants. In a separate study, Zangerl and Berenbaum () provided support for the natural enemy release hypothesis of plant invasion (Keane and Crawley , Mitchell and Power ) by measuring exotic plant defensive compounds before and after introduction of their co‐evolved herbivores.…”
Section: Contributions Of Herbaria To Global Change Researchmentioning
confidence: 99%
“…Elevated [CO 2 ] alters the nutritional quality of nectar rewards through direct effects on photosynthesis and sugar production (Watanabe et al, 2014). Increases in [CO 2 ] over the past 170 years also reduced pollen protein concentration in Solidago canadensis (Ziska et al, 2016). Such changes in either nectar or pollen rewards could adversely affect pollinators and the strength of pollinator-mediated selection on plant traits.…”
Section: Plant-pollinator Interactionsmentioning
confidence: 99%